CTLA-4 and PD-1 Control of T-Cell Motility and Migration: Implications for Tumor Immunotherapy - Brunner-Weinzierl, Monika C.; Rudd, Christopher E. (Frontiers in Immunology, 2018)
CTLA-4 is a co-receptor on T-cells that controls peripheral tolerance and the development of autoimmunity. Immune check-point blockade (ICB) uses monoclonal antibodies (MAbs) to block the binding of inhibitory receptors (IRs) to their natural ligands. A humanised antibody to CTLA- 4 [Ipilimumab] was first approved clinically followed by antibody blockade of PD-1 [Nivolumab and Pembrolizumab] and its ligand PD-L1 [Atezolizumab](Baumeister et al., 2016; Okazaki et al., 2013; Page et al., 2014; Sharma et al., 2011) The function and mechanisms of action of CTLA-4 involve cell intrinsic and cell extrinsic pathways. Effective anti-tumour immunity requires the activation of tumour-specific effector T cells, the blockade of regulatory cells and the migration of T-cells into the tumour. In this review, we review data implicating CTLA-4 and PD-1 in the motility of T-cells with a specific reference to the potential exploitation of theses pathways for more effective tumour infiltration and eradication.